Impact of Islamic leadership, motivation, and work-life balance on performance: a gender analysis - Suradi, Romi; Mamduh, Muhammad Faizul; Ali, Mohammad Mahbubi; Setianingsih, Hesti Eka; Cholil, Muhammad (Universitas Islam Indonesia, 2025)
Purpose – This study aims to analyze the effect of Islamic leadership on employee performance by integrating Islamic work motivation, work environment, and work-life balance (WLB) as mediating and contextual factors, while also examining gender differences through Multi-Group Analysis (MGA).